Morphologic study of male genitalia and female description of Schistopeltis lizeri Rehn (Blaberidae, Zetoborinae, Triboniini) - Del Carmen Valverde, Alejandra; Crespo, Francisco Antonio; Iglesias, Mónica Sandra (Zootaxa, 2012)
The genital sclerites of the male, the female and the mature nymph of Schistopeltis lizeri are described. The genitalia ofS. lizeri, S. microschistos and S. peculiaris are compared. The generic status of Schistopeltis is validated although it has close relationship with Tribonium.